Investigation of the mechanism of Xiaoyin Jiedu Yin in the treatment of psoriasis based on bioinformatics, machine learning - Fang, Ru-Nan; Zhou, Yang; Shen, Yang; Sun, Yuan; Li, Jian-Hong (Frontiers in Chemistry, 2025)
IntroductionPsoriasis is a chronic immune-mediated inflammatory skin disease. Xiaoyin Jiedu Decoction (XYJDY) is a traditional Chinese medicinal formula that has demonstrated significant clinical efficacy in alleviating psoriatic symptoms; however, its underlying pharmacological mechanisms remain unclear.MethodsWe employed network pharmacology, machine learning–based target screening, and functional enrichment to identify key targets and pathways. Single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics (ST) were used to validate gene expression. An IL-17A–induced HaCaT cell model was established for in vitro validation.ResultsAKR1B10 was identified as the core therapeutic target of XYJDY in psoriasis. It was markedly upregulated in psoriatic skin lesions, primarily enriched in keratinocytes, and its expression demonstrated positive correlations with multiple pro-inflammatory immune cell subsets. In vitro experiments showed that XYJDY-medicated serum significantly downregulated AKR1B10 expression in IL–17A–stimulated HaCaT cells.ConclusionThis study reveals that the multi-component formula XYJDY exerts anti-psoriatic effects through a multi-target synergistic mechanism, in which AKR1B10 is a potential core target. These findings provide a theoretical foundation for further exploration of the molecular mechanisms underlying the efficacy of XYJDY in psoriasis treatment.